Child with Deletion 9p Syndrome Presenting with Craniofacial Dysmorphism, Developmental Delay, and Multiple Congenital Malformations - Nirmala D. Sirisena; U. Kalpani S. Wijetunge; Ramya de Silva; Vajira H. W. Dissanayake (Case Reports in Genetics)
A 4-month-old Sri Lankan male child case with a de novo terminal deletion in the p22→pter region of chromosome 9 is described. The child presented with craniofacial dysmorphism, developmental delay, and congenital malformations in agreement with the consensus phenotype. A distinctive feature observed in this child was complete collapse of the left lung due to malformation of lung tissue. Cytogenetic studies confirmed terminal deletion of the short arm of chromosome 9 distal to band p22 [46,XY,del(9)(p22→pter)]. This is the first reported case of a de novo deletion 9p syndrome associated with pulmonary hypoplasia. This finding contributes to the widening of the spectrum of phenotypic features associated with deletion 9p syndrome.